A new species of Cnesterodon (Cyprinodontiformes: Poeciliidae) from a small tributary of arroyo Cuñá-Pirú, río Paraná basin, Misiones, Argentina - Aguiler, Gastón; Mirand, Juan Marcos; de Las Mercedes Azpelicuet, María (Zootaxa, 2009)
Cnesterodon pirai new species is described from a small stream, tributary of the arroyo Cuñá-Pirú, río Paraná basin in Argentina. The new species is diagnosed by the following combination of characters: 6 to 8 irregular dashes, ranging from oval to vertical stripes on females and 7 to 9 irregular dashes ranging from oval to circular dots on males; lack of a distal membranous filament on the terminal appendix of ray 3 of the gonopodium; absence of longitudinal dark-brown band along flank; snout long (16.7–28.7 % HL) and pointed; absence of a large post-gonopodium blotch on ventral profile in adult males; absence of dashes along predorsal portion of first, second and third lateral series of scales, associated to the vertical bars on body side; 12–13 epipleural ribs; medial surface of ascending process of premaxilla approximately straight; presence of teeth on fourth ceratobranchial; distal portion of third and fourth gonactinosts separate, except by tip of third gonactinost; fifth gonactinost free; and presence of a constriction on unpaired appendix of gonopodium. In a phylogenetic analysis the new species forms a tricotomy with (Cnesterodon brevirostratus + C. septentrionalis) and (C. hypselurus + C. iguape).